Zinc Fertilization on Zinc Dynamics, Availability and Uptake by Tomato-French Bean-Cucumber Cropping Sequence in an Alfisol - Rajendiran S.; H.B. Raghupathi; B.R. Raghu; R. Venugopalan (Journal of the Indian Society of Soil Science, 2025)
The objective of current investigation is to study direct and residual effects of Zn application on Zn fractions and availability in soil, yield and Zn uptake in tomato - french bean - cucumber system. One year field experiments were conducted during 2018-2019 in soil with DTPA extractable Zn of 0.88 mg kg-1. Treatments were one time soil application of 5, 10, 15 and 20 kg Zn ha-1 through ZnSO4.7H2O as basal dose only to tomato; foliar application of 0.5% ZnSO4.7H2O (two times 45 and 60 days after planting in each crop) and control (where Zn fertilization was not done). Crop yield was recorded and DTPA-Zn and Znfractions in soil were analyzed. Soil application of Zn had enhanced soil DTPA-Zn, total Zn content of soil, fruit and dry matter yields, however, beyond 10 kg ha-1 Zn application, significant yield improvement was not recorded. Soil Zn application increased Zn concentration and uptake. Foliar Zn spray did not show any significant change in yield and Zn uptake. Exchangeable-Zn and Zn associated with easily reducible Mn fractions of soil were largely contributed to Zn availability in soil and uptake. Soil application of 10 kg Zn ha-1 yr-1 is recommended in low Zn soils for enhancing productivity of vegetable systems with three crops raised in a year in sequence. However, when soil DTPA-Zn reaches 1.5 mg kg-1, the need based application of Zn to soil can be avoided because no yield response was found beyond this level.